Analysis of Corporate Social Responsibility (CSR) reports during the Covid-19 pandemic at Pertamina Laksda Adisucipto Yogyakarta - abel bimantara, Raka Abel Bimantara (COMMICAST, 2022)
The Indonesian government is working hard to reduce the impact of the spread of Covid-19. Of course, this requires support and encouragement from the Institution/private sector with adequate funding capacity. One of the SOEs that contributes actively in this funding sector is PT Pertamina (Persero). One of these studies aims to find out the Corporate Social Responsibility (CSR) report during the Covid-19 Pandemic at Pertamina Laksda Adisucipto Yogyakarta. The population in this study were all Pertamina Laksda Adisucipto Yogyakarta CSR reports, while the sample was Pertamina Laksda Adisucipto Yogyakarta CSR reports during the Covid-19 pandemic in 2021. Data collection methods were through interviews, documentation, and literature study. The data analysis used is semiotic analysis through the descriptive analytic paradigm of the meaning of symbols, words and sentences in Pertamina Laksda Adisucipto's CSR report in Yogyakarta. The results of the study show that there are programs that are fully diverted to efforts to handle Covid-19 in the City of Yogyakarta in 2021. This condition is a synergy between the Yogyakarta City Government and company managers for efforts to handle Covid-19 through the distribution of funds and food.